Smartphone addiction and sedentary lifestyle among university students: a correlation study - Handayani, Lina; Ahmad, Aditama Huzaifi; Novianti, Tria Nisa; Khalidah , Karimatul; Hafidz, Beddu (Jurnal Cakrawala Promkes, 2026)
Smartphone addiction is a global concern, especially in Indonesia. Many preteens use smartphones extensively, but university students are at risk due to their autonomy and reliance on them for academic and entertainment purposes. These variables prolong screen time, increasing smartphone addiction and a sedentary lifestyle. Smartphone addicts are 2.7 times more likely to be sedentary, and 90% of teens use them while sitting. About 50% of university public health students are sedentary. Therefore, this study aims to determine the relationship between smartphone addiction and sedentary lifestyle among university students. This study is an analytical, observational, cross-sectional design. The population included students in the Universitas Ahmad Dahlan Public Health Study Program (2021–2024 cohorts). Purposive sampling selected 95 active, smartphone-using, and willing students to complete the online questionnaire. The Indonesian Smartphone Addiction Scale – Short Version (SAS-SV) and Indonesian Adolescent Sedentary Activity Questionnaire examined smartphone addiction and sedentary lifestyle. Proofreading is shown in the Supplementary Materials for both translated, validated, and pilot-tested instruments. Spearman's Rho correlation test was used to analyze the data. Moderate smartphone addiction (64.21%) and sedentary lifestyle (42.11%) were common among students. Spearman's Rho correlation analysis demonstrated a modest, non-significant association between smartphone addiction and sedentary lifestyle (r = 0.090; p = 0.388; p > 0.05), indicating a very weak, non-significant relationship. Although smartphone addiction and sedentary lifestyle were not significantly related, moderate smartphone addiction remains concerning, suggesting interventions should also target environmental, social, and economic factors.